IPTEKS PERHITUNGAN POTENSI PENDAPATAN ASLI DAERAH (PAD) DI KOTA SEMARANG - Santoso, Aprih (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2020)
Regional revenue (PAD) aims to give authority to the Regional Government to fund the implementation of regional autonomy in accordance with the regional potential as a manifestation of decentralization. In the method of applying science and technology through predictions of the realization of regional revenue (PAD) in Semarang City for 2019 an increase in the realization of regional revenue (PAD) in 2013-2018 with an average percentage growth rate of 12.15 %, and produces predictions Semarang's regional revenue (PAD) for 2019 has increased to Rp 2.031.430.000.000.